Effect of the COVID-19 pandemic on utilization of essential health services in Iran evidence from an interrupted time series analysis - Mohammad Ranjbar; Seyed Masood Mousavi; Farzan Madadizadeh; Nahid Hosseini Dargani; Samaneh Iraji; Blake Angell; Yibeltal Assefa (BMC, 2024)
Abstract Background The COVID-19 disrupted the provision of essential health services in numerous countries, potentially leading to outbreaks of deadly diseases. This study aims to investigate the effect of the COVID-19 pandemic on the utilization of essential health services in Iran. Methods An analytical cross-sectional study was conducted using interrupted time series (ITS) analysis. Data about five indicators, including 'childhood vaccination, infant care, hypertension screening, diabetes screening, and breast cancer screening,' were obtained from the electronic health record System in two-time intervals: 15 months before (November 2018 to January 2020) and 15 months after (January 2020 to May 2021) the onset of the COVID-19 pandemic. The data were analyzed by utilizing ITS. In addition, a Poisson model was employed due to the usage of count data. The Durbin-Watson (DW) test was used to identify the presence of lag-1 autocorrelation in the time series data. All statistical analysis was performed using R 4.3.1 software, considering a 5% significance level. Results The ITS analysis showed that the COVID-19 pandemic significantly affected the utilization of all essential health services (P < 0.0001). The utilization of hypertension screening (RR = 0.51, p < 0.001), diabetes screening (RR = 0.884, p < 0.001), breast cancer screening (RR = 0.435, p < 0.001), childhood vaccination (IRR = 0.947, p < 0.001), and infant care (RR = 1.666, p < 0.001), exhibited a significant decrease in the short term following the pandemic (P < 0.0001). However, the long-term trend for all service utilization, except breast cancer screening (IRR = 0.952, p < 0.001), demonstrated a significant increase. Conclusions The COVID-19 pandemic affected utilization of essential health care in Iran. It is imperative to utilize this evidence to develop policies that will be translated into targeted planning and implementation to sustain provision and utilization of essential health services during public health emergencies. It is also vital to raise awareness and public knowledge regarding the consequences of interruptions in essential health services. In addition, it is important to identify the supply- and demand-side factors contributing to these disruptions.